Diversity and bioprospecting of cultivable fungal assemblages in sediments of lakes in the Antarctic Peninsula. Issue 6 (June 2020) - Ogaki, Mayara B.; Teixeira, Daniela R.; Vieira, Rosemary; Lírio, Juan M.; Felizardo, João P.S.; Abuchacra, Rodrigo C.; Cardoso, Renan P.; Zani, Carlos L.; Alves, Tânia M.A.; Junior, Policarpo A.S.; Murta, Silvane M.F.; Barbosa, Emerson C.; et al.
Abstract: We recovered 195 fungal isolates from the sediments of different lakes in the Antarctic Peninsula, which were screened to detect bioactive compounds. Forty-two taxa belonging to the phyla Ascomycota, Basidiomycota, and Mortierellomycota were identified. Thelebolus globosus, Antarctomyces psychrotrophicus, Pseudogymnoascus verrucosus, Vishniacozyma victoriae, and Phenoliferia sp. were found to be the most prevalent. The fungal assemblages showed high diversity and richness, but low dominance values. However, the diversity indices and fungal distribution ranged according to the different lake sediments. Sixty fungal extracts displayed at least one biological activity against the evaluated targets. Among them, Pseudogymnoascus destructans showed selective trypanocidal activity, Cladosporium sp. 1 and Trichoderma polysporum showed antifungal activity, and Pseudogymnoascus appendiculatus and Helotiales sp. showed high herbicidal activity. We detected a rich and diverse fungal community composed of cold cosmopolitan and psychrophilic endemic taxa recognized as decomposers, symbiotics, pathogens, and potential new species, in the sediments of Antarctic lakes. The dynamics and balance of this fungal community represents an interesting aquatic web model for further ecological and evolutionary studies under extreme conditions and potential climate changes in the regions. In addition, we detected fungal taxa and isolates able to produce bioactive compounds that may represent the source of prototype molecules for applications in medicine and agriculture. Graphical abstract: Image 1 Highlights: We access fungi present in the sediments of lakes of Antarctica. Taxa belonging to cold cosmopolitan and psychrophilic endemic taxa. Fungi demonstrated trypanocidal, herbicidal, and antifungal activities. Decomposers, symbiotics, pathogens, and potential new species were detected.